The visual poetics of La Muralla Roja - Mena García, Enrique (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2023)
In recent years we have witnessed a visual flood of the emblematic work of Taller de Arquitectura, a multidisciplinary group that gathers around the figure of Ricardo Bofill, called La Muralla Roja (Calpe, Alicante). As the 50th Anniversary of this media icon approaches, we see almost no scientific investigation into its advertising appeal. Because its importance increases at times, the building is analyzed and repositioned from an aesthetic and advertising vision in a sharp rise in Social Media, whose architecture is still so current, and a diversity of artistic currents are interested in it.